O empoderamento dos indivíduos na mediação de conflitos como instrumento de efetivação da busca da felicidade - Vitale, Carla Maria Franco Lameira (2018)
The public policy for the adequate treatment of conflicts, instituted by the Resolution 125/2010 of the National Council of Justice, presents mediation as an effective method of handling controversies, which favors the participation of the parties in the construction of the solution. It's a procedure that is closer to access to the justice, to value the participation of individuals, as true protagonists of the best solution to be built, with emphasis on the interests, needs and feelings of the people involved in the conflict environment. The researches about mediation highlights the importance of communication for the development of constructive dialogues and the empowerment of the parties. The deepening in this study, even under the approach given by the philosopher Jürgen Habermas, in developing the Theory of Communicative Action, is adequate to what we can investigate in which contexts the communication can provoke the behavior transformation of people and, consequently, of society , in order to achieve the social pacification through the formation of legitimate consensus. It is relevant, therefore, to highlight the connection established between the empowerment of individuals in mediation as an instrument for effecting the pursuit for happiness, a fundamental right.